Exploring Researchers' Perspectives on Institutional Review Boards Functions in Saudi Arabia: A Survey Utilizing the IRB-RAT Tool - AlFattani, Areej; AlShahrani, Asma; AlBedah, Norah; Alkawi, Ammar; AlMeharish, Amani; Altwaijri, Yasmin; Omar, Abeer; AlKawi, M Zuheir; Khogeer, Asim (BMC medical ethics, 2025)
The ethics committee has the responsibility to comply with the rules and guidelines regarding oversight of all human research activities, particularly when the research study involves vulnerable people. It also has the role of educating researchers on ethical issues, scientific truthfulness, preventing misconduct and conflicts of interest. In our study we evaluate and benchmark the function of the local ethical committees across the country from the researchers point-of-view. We employed an online IRB-RAT survey to measure perspectives of investigators towards IRB functions dealing with fairness issues, services, bias, and competences and upholding the rights of the human participants. Two responses were recorded: first shows how important an IRB function is for the investigator in his work, second shows how researchers rate their IRBs in being descriptive in that specific function. The difference of these two scores represent the outcome. We had 179 participants, 166(94%) researchers/research coordinators, and 13(7.2%) IRB members, 94 (53%) participants had been working in the research field for more than 11 years, and the majority 163(90%) revealed that they had IRB contact. The largest gap between actual rating and ideal was observed for the item "An IRB that requires that its chair be an experienced investigator" with a score difference of 1.53. In contrast, the smallest score difference was for the item "Considering the protection of human participants," which had a score of 0.51. According's to researchers point of view; IRBs respect researchers, view human protections as a primary role, do not allow personal bias, maintain accurate records and take timely action whenever misconduct is reported. Further collaborations are needed to enhance IRB performance and to engage researchers in more productive communication with their IRBs.